Efficient energy recovery from wastewater with high rate activated sludge process: oversights and misguidances - Orhon, Derin; Çokgör, Emine Ubay; Sözen, Seval (Journal of chemical technology and biotechnology (1986), 2023)
Background The major aim of the study was to define a scientific framework to evaluate energy recovery from domestic wastewater, based on model assessment of process stoichiometry and kinetics using relevant experimental data. The evaluation was tailored to reveal and explain all the oversights and misconceptions on the subject. A new approach was adopted to focus specifically on a paper by Liang et al. (2022) to better visualize and indicate scientific ways to remedy the key misguidances. The alternative appraisal utilized the latest available support in terms of the database for chemical oxygen demand (COD) fractionation and process kinetics. Results The evaluation first demonstrated the inherent deficiencies of high rate activated sludge (HRAS) configurations such as the sequencing batch reactor and contact stabilization; then, it presented a new way to define excess sludge components in terms of fractions of the influent COD, indicating the major handicap for energy recovery and biomass loss in the effluent due to gravity settling. Effective energy conservation was computed to remain between 17% and 37% when the sludge age was reduced from 2.0 d down to 0.5 d. Conclusions The study offered conclusive proof that the contact stabilization process with gravity settling was, in fact, inherently unsuitable for energy conservation. Instead, the emerging scientific approach proposed a single‐volume HRAS system with membrane filtration replacing gravity settling. An equally valid suggestion was to replace anaerobic technology for energy recovery with thermochemical technologies, such as high‐rate pyrolysis, with a much higher energy recovery potential. © 2022 Society of Chemical Industry (SCI).